Respuesta :

Answer:

Part 1) [tex]y=-2x-1[/tex]

Part 2) [tex]y=-(1/2)x+(5/2)[/tex]

Step-by-step explanation:

Part 1)

we know that

If two lines are perpendicular

then

the product of their slopes is equal to minus one

so

[tex]m1*m2=-1[/tex]

Find the slope of the given line

we have

[tex]y=\frac{1}{2}x-1[/tex]

the slope of the given line is [tex]m1=(1/2)[/tex]

Find the slope of the line perpendicular to the given line

[tex](1/2)*m2=-1[/tex]

[tex]m2=-2[/tex]

Find the equation of the line into slope intercept form

[tex]y=mx+b[/tex]

we have

[tex]m=-2[/tex]

[tex]point (-2,3)[/tex]

substitute and solve for b

[tex]3=-2(-2)+b[/tex]

[tex]3=4+b[/tex]

[tex]b=-1[/tex]

The equation is equal to

[tex]y=-2x-1[/tex]

Part 2)

we know that

If two lines are perpendicular

then

the product of their slopes is equal to minus one

so

[tex]m1*m2=-1[/tex]

Find the slope of the given line

we have

[tex]y+1=2(x-3)[/tex] -----> equation of the line into point slope form

the slope of the given line is [tex]m1=2[/tex]

Find the slope of the line perpendicular to the given line

[tex](2)*m2=-1[/tex]

[tex]m2=-(1/2)[/tex]

Find the equation of the line into slope intercept form

[tex]y=mx+b[/tex]

we have

[tex]m=-(1/2)[/tex]

[tex]point (5,0)[/tex]

substitute and solve for b

[tex]0=(-1/2)(5)+b[/tex]

[tex]b=5/2[/tex]

the equation is equal to

[tex]y=-(1/2)x+(5/2)[/tex]